9 is 60000
and 11 is 600km is larger
Answer:
A and C
Step-by-step explanation:
<h3>A</h3>
![= \sqrt{ {5}^{2} + ( \sqrt{6})^{2} } \\ = \sqrt{25 + 6} \\ = \sqrt{31}](https://tex.z-dn.net/?f=%20%3D%20%20%5Csqrt%7B%20%7B5%7D%5E%7B2%7D%20%2B%20%28%20%5Csqrt%7B6%7D%29%5E%7B2%7D%20%20%7D%20%20%5C%5C%20%20%3D%20%20%5Csqrt%7B25%20%2B%206%7D%20%20%5C%5C%20%20%3D%20%20%5Csqrt%7B31%7D%20)
<h3>C</h3>
![= \sqrt{ {9}^{2} + {12}^{2} } \\ = \sqrt{81 + 144} \\ = \sqrt{225} \\ = 15](https://tex.z-dn.net/?f=%20%3D%20%20%5Csqrt%7B%20%7B9%7D%5E%7B2%7D%20%2B%20%20%7B12%7D%5E%7B2%7D%20%20%7D%20%20%5C%5C%20%20%3D%20%20%5Csqrt%7B81%20%2B%20144%7D%20%20%5C%5C%20%20%3D%20%20%5Csqrt%7B225%7D%20%20%5C%5C%20%20%3D%2015)
Multiply everything in the second parenthesis by x.
-3x^3 + 3x^2 + x
Multiply everything in the second parenthesis by 2.
-6x^2 + 6x + 2
Combine these two equations together.
-3x^3 + 3x^2 + x - 6x^2 + 6x + 2
Combine like terms.
-3x^3 - 3x^2 + 7x + 2
Hope this helps!
<span />
Answer:
This is a right triangle
Step-by-step explanation:
We will use the Pythagorean theorem
a^2 + b^2 = c^2
If this is true it is a right triangle
5^2 + 12^2 = 13^2
25+144 = 169
169 =169
This is true so this is a right triangle